Un Deu Enemi. Jews and Judaism in French and English Medieval Illuminated Manuscripts in the Royal Library - Vidas, Marina (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2016)
Marina Vidas: Un Deu Enemi. Jews and Judaism in French and English Medieval Illuminated Manuscripts in the Royal Library The article analyzes images of and texts about Jews and Judaism in five medieval illuminated manuscripts in the collection of the Royal Library, Copenhagen. I begin by examining the references to Jews in a bestiary (MS GKS 3466 8º) composed in the twelfth century by Philippe de Thaon for Queen Adeliza of England and copied a century later in Paris. Then I analyze depictions of Jews in a French early thirteenth-century personal devotional manuscript (MS GKS 1606 4º) as well as in a number of related de luxe Psalters and Bibles in foreign collections. Textual references to Judaism and Jews are examined in a compilation of saints’ lives (MS Thott 517 4º) as well as depictions of individuals of this faith in an Hours (MS Thott 547 4º), both made in fourteenth-century England for members of the Bohun family. Lastly, I analyze images illustrating legends derived from the Babylonian Talmud in a Bible historiale (MS Thott 6 2º), executed for Charles V of France (r. 1364–1380). I argue that images depicting Jews in narrative cycles had a number of meanings, some of which can be interpreted as anti-Jewish. I suggest that the images also played a role in shaping the piety of their audiences as well as the intended viewers’ understanding of their social identity. Indeed, depictions of Jews in the manuscripts seem mostly unrelated to the actually existing Jews. Members of the Hebrew faith were often represented in contexts in which their appearance, beliefs, and activities were distorted to emphasize the holiness, goodness, and perfection of Christ and the Virgin Mary. It is also suggested that their representations may have spurred a reflection on, and sometimes even a criticism of, Christian behavior and attitudes.